The road to UiTM Sarawak Campus's website launching - Abdul Rahim, Mohd. Zamri; Lee, Beng Yong (Universiti Teknologi MARA, Sarawak, 2004)
UiTM Sarawak started developing its own website in 1998 with the help of PM Wan Akil Wan Abdullah. The responsibility was handed over to PM Ahmad Ismail in 2003. Currently it is being managed by En Mohd. Zamri B. Abdul Rahim An ad hoc website development committee called Underground Spidey was formed with a group of lecturers and supporting staff headed by En Zamri and Pn Ziraizratul to design and develop the website structure for UiTMSarawak. The committee is made up of two teams - technical and non-technical. The technical team is formed by lecturers from the department of Computer Sciences with supports from the Faculty of Electrical Engineering whereas the non-technical team consisted of lecturers from various department such as Accounting, Information Management, Engineering, and Language.